Pengaruh Political Connections dan Sistem Manajemen Lingkungan Terhadap Kinerja Lingkungan - Asya'bani, Dzaqiyul Fuadzi; Jayanti, Dwi (Akuisisi : Jurnal Akuntansi, 2025)
The output of this research is to analyze the effect of Political Connections and Environmental Management Systems on Environmental Performance. This research uses quantitative techniques and carries out analysis using descriptive methods. Data and information for this research comes from Annual Reports or Sustainability Reports of Mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. This research uses purposive sampling as a data processing approach. The research sample consisted of 10 companies, each with 50 samples. The data was examined using descriptive statistical techniques, this method involves testing classical assumptions which include testing data normality, heteroscedasticity, multicollinearity and autocorrelation. After that, the data was tested using multiple linear regression, then correlation and determination coefficient analysis was carried out by testing the hypothesis using the t-statistical test and the F-statistical test. The results of this research show that Political Connections and Environmental Management Systems have a positive and significant influence on Environmental Performance. The findings of this research indicate that Political Connections and Environmental Management Systems have a beneficial and substantial impact on Environmental Performance